Refleksi Diri untuk Memperbaiki Hasil Belajar berdasarkan Hasil TIMSS - Fahmi, NFN; Purwati, Rumondang (Pusat Asesmen dan Pembelajaran, 2019)
The aim of this study is to obtain information about the mathematics competency of Indonesian students based on international benchmark in TIMSS 2011. This study is a quantitative descriptive study based on TIMSS 2011 data. The population of this study is all students in the junior high schools (SMP) in Indonesia. The subjects of the research are 5.795 Indonesian students from 154 schools. The methods of multistage stratified and random sampling are conducted as sample-determining technic. Data analysis was administered by International Association for the Evaluation of Educational Achievement (IEA) using IDB analyzer program.The average mathematics score acquired by Indonesian students is 386, below the international average score (500). Indonesian students is at rank 40 of 45. Based on international benchmark, there are 0% Indonesian students who can achieve advanced level, 2% reaching the high level, 15% achieving intermediate level, and 43% in the low level. For most of Indonesian students the mastery of Mathematics material is very low, especially in solving the problem at proficient level and high level. The research concludes that: (1) Indonesian students are less accustomed to work on items in applying and reasoning cognitive domain, especially in constructed-response items; (2) Indonesian students are less accustomed to work on items that need more than one process of solving the questions; (3) Misconception among Indonesian students about arithmetic operations (+, -, x, :), which one should be done first; and (4) Indonesians students have more difficulties in working on algebraic operations than number operations.Abstract. The aim of this study is to obtain information about the mathematics competency of Indonesian students based on international benchmark in TIMSS 2011. This study is a quantitative descriptive study based on TIMSS 2011 data. The population of this study is all students in the junior high schools (SMP) in Indonesia. The subjects of the research are 5.795 Indonesian students from 154 schools. The methods of multistage stratified and random sampling are conducted as sample-determining technic. Data analysis was administered by International Association for the Evaluation of Educational Achievement (IEA) using IDB analyzer program.The average mathematics score acquired by Indonesian students is 386, below the international average score (500). Indonesian students is at rank 40 of 45. Based on international benchmark, there are 0% Indonesian students who can achieve advanced level, 2% reaching the high level, 15% achieving intermediate level, and 43% in the low level. For most of Indonesian students the mastery of Mathematics material is very low, especially in solving the problem at proficient level and high level. The research concludes that: (1) Indonesian students are less accustomed to work on items in applying and reasoning cognitive domain, especially in constructed-response items; (2) Indonesian students are less accustomed to work on items that need more than one process of solving the questions; (3) Misconception among Indonesian students about arithmetic operations (+, -, x, :), which one should be done first; and (4) Indonesians students have more difficulties in working on algebraic operations than number operations.AbstrakTujuan penelitian ini adalah memperoleh informasi tentang kemampuan matematika siswa Indonesia berdasarkan benchmark Internasional dalam TIMSS 2011. Penelitian ini merupakan penelitian deskriptif kuantitatif berdasarkan data TIMSS tahun 2011. Populasi dari penelitian ini adalah seluruh siswa SMP/MTs dan sampel penelitian adalah siswa kelas VIII SMP/MTs. Jumlah siswa yang menjadi sampel sebanyak 5.795 siswa dari 154 sekolah. Penentuan sampel dilakukan dengan metode multistage stratified dan acak. Analisis data dilakukan oleh International Association for the Evaluation of Educational Achievement (IEA) menggunakan program IDB analyzer. Rerata skor matematika siswa Indonesia adalah 386, di bawah rerata skor Internasional (500). Indonesia berada pada peringkat 40 dari 45 negara peserta. Capaian siswa Indonesia untuk level mahir 0%, level tinggi 2%, level menengah 15%, dan level rendah 43%. Penguasaan materi matematika bagi sebagian besar siswa Indonesia masih sangat rendah terutama untuk menyelesaikan soal-soal pada level mahir dan level tinggi. Simpulan dari penelitian ini adalah: (1) siswa Indonesia masih menemui kesulitan untuk menyelesaikan soal aplikasi dan penalaran, terutama untuk soal uraian, (2) dalam konsep operasi hitung (+, - , x, : ) masih ditemukan siswa yang belum memahami urutan oprerasi hitung yang dikerjakan terlebih dahulu, dan (3) siswa Indonesia masih kesulitan menyelesaikan soal dalam bentuk variabel atau operasi aljabar.